Cumplimiento de las normas de bioseguridad por el personal de salud del servicio de neonatología. Hospital Regional Docente de Trujillo - Vásquez Gutiérrez, Julia Mary Carmen (2016)
This research study descriptive, cross-sectional, was performed in the service of Neonatology, Regional Hospital of Trujillo in the months of October 2015- February 2016, in order to determine compliance with biosafety standards in processes of basic procedures, use of personal protection, hand washing, use of mask and cap mandilón by health personnel neonatology service. The sample consisted of 82 people from the health personnel working in the neonatology service. The conclusions are: Compliance with biosafety standards in the process of general procedures, mostly is nurses 66.6 percent, nursing techniques at 63.6 percent, internal nursing 62.5 percent, health 52 percent, medical interns 40 hundred. Compliance with biosafety standards in the use of protective elements, is mostly in groups of nurses (84 percent), techniques Nursing (81.8 percent), internal nursing (62.5 percent), internal medicine ( 60.0 percent), Compliance with biosafety standards in the process of hand washing, is mostly by nurses, internal nursing, nursing techniques (90.9 percent, 87.5 percent, 72.7 percent, respectively) and not largely meet doctors and internal medicine (66.0 percent, 60.0 percent, respectively). Compliance with biosafety standards in the use of cap, mask and mandilón process, mostly by the nursing team, including nurses, nursing techniques, internal nursing (87.9 percent, 81.8 percent, 75.0 percent respectively), the group does not meet are internal medicine and doctors (80.0 percent, 64.0 percent,